2009
DOI: 10.4103/0250-474x.57282
|View full text |Cite
|
Sign up to set email alerts
|

Solid lipid nanoparticles: A modern formulation approach in drug delivery system

Abstract: Solid lipid nanoparticles are at the forefront of the rapidly developing field of nanotechnology with several potential applications in drug delivery, clinical medicine and research, as well as in other varied sciences. Due to their unique size-dependent properties, lipid nanoparticles offer the possibility to develop new therapeutics. The ability to incorporate drugs into nanocarriers offers a new prototype in drug delivery that could be used for secondary and tertiary levels of drug targeting. Hence, solid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
390
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 746 publications
(434 citation statements)
references
References 46 publications
5
390
0
4
Order By: Relevance
“…Indeed, nanocarriers such as lipid micelles (Neuberg et al, 2015), solid lipid nanoparticles (Mukherjee et al, 2009;Bunjes, 2010), nanostructured lipidic carriers (NLCs) (Khan et al, 2015) and lipid nanocapsules (Sánchez-Moreno et al, 2012) have already been reported to hold immense promise for oral delivery of poorly water-soluble bioactives. Amongst these nanocarriers, the NLCs are considered to be of wider interest owing to their high drug-loading efficiency and drug stability (Naseri et al, 2015;Shah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nanocarriers such as lipid micelles (Neuberg et al, 2015), solid lipid nanoparticles (Mukherjee et al, 2009;Bunjes, 2010), nanostructured lipidic carriers (NLCs) (Khan et al, 2015) and lipid nanocapsules (Sánchez-Moreno et al, 2012) have already been reported to hold immense promise for oral delivery of poorly water-soluble bioactives. Amongst these nanocarriers, the NLCs are considered to be of wider interest owing to their high drug-loading efficiency and drug stability (Naseri et al, 2015;Shah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…KLN'ler güvenli ve etkili bir şekilde gen ve ilaç türevi taşıyabilen nanotaşıyıcılardır. Diğer taşıyıcı sistemlere göre; lipofilik ve hidrofilik ilaçlarla kolaylıkla birleşebilme, gelişmiş fiziki stabiliteye sahip olma, kontrollü ilaç ve gen serbestlenmesini sağlama, biyolojik uyumluluk, bölgeye spesifik ilaç etkinliği gibi birçok avantajları sahip olduğundan, önemli bir nanotaşıyıcı olarak gösterilmektedir (44).…”
Section: İlaç Taşiyici Si̇stemler Olarak Nanotaşiyicilarunclassified
“…The common excipients used in SLN formulation are solid lipids, emulsifiers, co-emulsifiers and water [46] . They display major advantages such as controlled release, improved bioavailability, protection of chemically labile molecules, cost effective excipients, enhanced drug incorporation and extensive application range [47] . SLNs represent an interesting alternative to traditional colloidal carriers, such as emulsions, liposomes and polymeric nanoparticles.…”
Section: Delivery Routes and Its Challenges Of Ocular Drug Deliverymentioning
confidence: 99%